KINETICS OF CATALYTIC SYNTHESIS OF DIMETHYL ETHER FROM SYNTHESIS GAS - Бахтиёров Дилшод Бекзодович; Шукуров Жасур Хошимович; Абиджон Тилляев Джуракулович (American Journals Publishing, 2025)
In this work, the effect of various factors on the process of direct synthesis of dimethyl ether from synthesis gas in one stage on the catalyst CuO‧ZnO‧Al2O3‧ZrO2/bentonite was studied. As a result of the studies of the influence of various factors on the yield of target products in the process of obtaining dimethyl ether from synthesis gas, it was found that an increase in the molar ratio, pressure, temperature and molar ratio of hydrogen to greenhouse gas leads to an increase in the conversion of greenhouse gases due to the fact that the reaction of direct synthesis of dimethyl ether from synthesis gas prevails.